The Relationship between Andropause and Anxiety in males in Jebres Subdistrict, Surakarta - Raja Amelia Putriana; Andri Iryawan; Slamet Riyadi (Nexus Kedokteran Komunitas, 2012)
Background: Andropause is a changes that occurs due to males because of reduction of testosterone levels. These changes is not only in the physical aspect, but also the psychological aspect. This study aims to determine the relationship between andropause with anxiety in males.Method: This research is a analytical observational research with the approach of cross sectional. The sample was taken using purposive random sampling after being selected based on the inclusion and exclusion criteria of research and the sample could not be selected when the result of L-MMPI ? 10. The subject filled in (1) curriculum vitae form and informed consent, (2) L-MMPI questionnaire to find out the respondents truthfulness in filling in questionnaire, (3) ADAM questionnaire as an early screening andropause and (4) T-MAS questionnaire to find out the anxiety score. 60 subject of research were obtained as the data and analyzed using with Chi Square and Coefisien Contingency (C).Result: The data analysis, with ? = 0,05, shows p = 0,06 which means p > 0,05 and C = 0,324 or 32,4%.Conclusion: This study revealed that there is no significant correlation between andropause and anxiety in males (p > 0,05).Keywords: Andopause, Anxiety